A non-cooperative game theoretic framework for frequency channel sharing problem - Hung, Nicholas Kok Liang (2014)
Cognitive radio technology is a revolutionary communication paradigm that utilizes existing wireless spectrum resources more efficiently, yet at the same time introduces the complexity of human users that are intelligent and have the ability to observe, learn and act to optimize their performance with regards to these resources that are available. The aim of this project is to model and simulate these rational users that aim to maximise their own performance in spite of all the other users doing exactly the same thing in the context of the frequency channel sharing problem in a non-cooperative framework using game theory.